Adult Education and Work Contexts: International Perspectives and Challenges Comparative Perspectives from the 2017 Wuerzburg Winter School - Egetenmeyer, Regina; Fedeli, Monica (Studien zur Paedagogik, Andragogik und Gerontagogik / Studies in Pedagogy, Andragogy, and Gerontagogy, 2018)
Adult education has deep connections with employment contexts. This volume discusses interrelations within transnational contexts studied during the Würzburg Winter School on Comparative Studies in Adult Education and Lifelong Learning (COMPALL). The book shows that adult education and work contexts are influenced by international and transnational developments. The findings are presented in three chapters: Lifelong Learning Policies Targeting Employment Contexts; Transnational Perspectives on Lifelong Learning Policies; Employment Perspectives and Professionalisation in Adult Education.